ARTIFICIAL INTELLIGENCE IN ISLAMIC EDUCATION AND ISLAMIC CULTURE FOR STUDENTS’ ACADEMIC AWARENESS - Ngatmin Abbas; Iffah Mukhlisah (Jurnal As-Salam, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed learning practices in higher education, including the ways students access, process, and present academic knowledge. This study aims to examine institutional support for coding and AI learning, explore students’ perceptions of AI, analyze the transformation of students’ academic awareness amid the use of AI, and reconstruct its utilization within the framework of Islamic education and Islamic culture. This research employed a descriptive quantitative approach with a survey design. The participants were 108 students from several private universities in Surakarta and its surrounding areas. Data were collected through an online questionnaire and analyzed using descriptive statistics, including tabulation, percentages, and contextual interpretation. The findings reveal that institutional support for coding and AI learning remains moderate, and students’ understanding of basic AI concepts is similarly moderate. At the same time, most students perceive AI as relevant in supporting academic work in logical, critical, and systematic ways. However, the use of AI cannot be separated from the need to strengthen academic ethics, critical literacy, and a culture of verification. This study concludes that Islamic education and Islamic culture provide an important normative foundation for directing the use of AI so that it serves not merely as a tool of technological efficiency, but also as a means of cultivating students’ critical, reflective, and morally responsible academic awareness.